AB0187 Estrogen-Induction of STAT1 and STAT4 Expression by Estrogen Receptor Alpha Suggests a Novel IFN-Alpha-Independent Mechanism of Sex-Bias in Systemic Lupus Erythematosus Pathogenesis. (10th June 2014) - Young, N.A.; Wu, L.-C.; Burd, C.; Bruss, M.; Valiente, G.; Jarjour, W.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a devastating multi-organ autoimmune disease displaying an overwhelming female predilection. Estrogen (E2) influences gene expression by binding to estrogen receptors (ERα and ERβ) and has been suggested in SLE pathogenesis. Further, E2 has been shown to regulate Signal Transducer and Activator of Transcription (STAT) 1 and STAT4 function, and to have known associations with SLE. Toll-like receptor 8 (TLR8) has also been implicated in SLE and is a potent inflammatory mediator. Objectives: In this study, our aim was to demonstrate the E2-mediated induction of STAT1 and STAT4 for the first time in primary human peripheral blood mononuclear cells (PBMCs) and mechanistically characterize the pathway that is operative in this induction. Methods: Putative estrogen response elements (EREs) in the human genome were identified from ChIP-seq data of MCF-7 cells stimulated with E2 for 45 min. PBMCs isolated from SLE patients and healthy controls were treated with a physiological dose of E2. Radio-labeled probes corresponding to STAT1 DNA binding regions were used in EMSA analysis to examine DNA-protein complex formation in a human monocytic cell line (THP-1), which lacks detectable IFNα expression. In the presence of E2, siRNA was used to block ERα, IFNα, or STAT1 expression in primary human macrophages or THP-1 cells. Results: STAT1 is located just upstream of STAT4 and ChIP-seq data revealed an intragenic ERE binding peak within the STAT1 locus with E2 treatment, suggesting that ERα may be promoting the expression of both genes (Fig 1 ). To demonstrate E2-mediated induction of STAT1 and STAT4, primary human PBMCs from SLE patients and healthy controls were treated with a physiological dose of E2. Expression of STAT1 and STAT4 was significantly induced relative to untreated controls. Given that we have previously observed that TLR8 expression is higher in SLE and induced with E2 treatment, a bona fide STAT1 binding region proximal to the TRL8 gene was used in EMSA analysis and showed enhanced DNA-protein complex formation with E2 stimulation. Moreover, siRNA blocking STAT1 significantly reduced E2-mediated TLR8 induction. In primary human cells and in a hematopoietic cell line, siRNA blocking ERα inhibited STAT1 and STAT4 induction with E2 stimulation, while targeting IFNα had no effect. Conclusions: E2 can stimulate the expression of STAT1 and STAT4 in PBMCs and subsequently could lead to the pathogenesis observed in SLE due to their potent signal transducing effects over the immune system. Additionally, the identification of molecular targets to inhibit the TLR8 inflammatory pathway presents a significant therapeutic opportunity. Collectively, our results indicate that STAT1 and STAT4 may contribute to the E2-mediated sex-bias observed in autoimmunity through ERα signaling and may potentially be ideal targets in future therapy to treat SLE. Acknowledgements: We would like to extend our appreciation to all the volunteers that participated in this study. Our research would not be possible without the time and effort they put forth. We would also like to thank the Center for Clinical and Translational Science's Research Match program at OSUWMC and the American Red Cross. Both organizations were instrumental in the progress of our research. Funding for this work provided through NIDDK K23DK059850, NIEHS R00ES019918, and the Wexner Medical Center at The Ohio State University. Funding for the Center for Clinical and Translational Science provided through CTSA grant number UL1TR000090. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3909